PEMBERIAN MILKSHAKE PISANG SEBELUM LATIHAN TERHADAP KELELAHAN DAN TEKANAN DARAH ATLET SEPAK BOLA - Linda Ustafia; Susi Tursilowati; Astidio Noviardhi (JURNAL RISET GIZI, 2017)
Background  : Fatigue is affected by decreased muscle glycogen and decreased blood flow to muscle. In addition, dilation and constriction of blood vessels during exercise also affects blood pressure. Bananas are a source of carbohydrates and potassium. Carbohydrates are used to energy and potassium are used to regulate heart rate and maintain fluid and electrolyte balance. Calcium in milk can help muscle contraction during exercise.Objective  : to determine the effect of banana milkshake on fatigue and blood pressure in football athletes.Methods  : true experiment study with pre and post only control group design. Subjects of this study is 14 football athletes were randomly divided into 2 groups: the control group given banana and the treatment group given the banana milkshake. Fatigue at soccer athletes in PS Undip was measured with a harvard step test by calculating the Body efficiency index and blood pressure measured before and after the test. Data were analyzed by independent t-test and paired t-test.Results  : Mean Body Efficiency Index (VO2max) before treatment in treatment group 89.85 ± 8.46 and after treatment 92.41 ± 9.813 and in control group before treatment 94.45 ± 11.596 and after treatment 99.01 ± 8.325. The difference of systolic and diastolic blood pressure in treatment group before treatment was 19.43 ± 22.44 and 0.00 ± 7.68 while in control group 19.28 ± 14.96 and 2.71 ± 10.68. After treatment in treatment group 30.57 ± 18.88 and 2.143 ± 10,023 while control group 13.43 ± 18.15 and 6.28 ± 18.98.Conclusion  : There is no effect of banana milkshake on fatigue and blood pressure. Bananas are more effective than banana milkshakes.